2019
DOI: 10.1016/j.amsu.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder (PTSD) among Filipino boys subjected to non-therapeutic ritual or medical surgical procedures: A retrospective cohort study

Abstract: In the Philippines, non-therapeutic genital cutting is viewed as a culturally sanctioned rite of passage from boyhood to manhood. Strong social and peer pressure is exerted on boys aged between 8-16years to submit to destructive genital cutting, despite the fact that many men who have been subjected to genital cutting during infancy or childhood often describe their experiences in the language of violence, torture, mutilation, and sexual assault. Among a group of 505 Filipino boys subjected to ritual genital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Besides Indonesia, other nations such as the Philippines also practice mass circumcision. [ 20 ] This study revealed that most parents believed that activity involving lots of people are still unsafe and could potentially spread the COVID-19 infection, as evidenced by the majority of parents forbidding their sons from engaging in mass circumcision while the COVID-19 pandemic is ongoing. However, by applying health protocols, screening and rapid circumcision techniques, free mass circumcision was successfully carried out in several areas of Indonesia without any local transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Indonesia, other nations such as the Philippines also practice mass circumcision. [ 20 ] This study revealed that most parents believed that activity involving lots of people are still unsafe and could potentially spread the COVID-19 infection, as evidenced by the majority of parents forbidding their sons from engaging in mass circumcision while the COVID-19 pandemic is ongoing. However, by applying health protocols, screening and rapid circumcision techniques, free mass circumcision was successfully carried out in several areas of Indonesia without any local transmission.…”
Section: Discussionmentioning
confidence: 99%